Making data review by a novel calculation algorithm for detecting objects’ views - Tarimer, Ilhan; Karadaǧ, Buse Cennet; Flieger, Michał (Wykonywanie przeglądu danych przez nowoczesny algorytm obliczeniowy do wykrywania widoków obiektów, 2021)
In this study, an image processing was performed with a software developed in Python programming language by capturing object views. In this context, an algorithm was created to calculate the amount of substance in a particular container at a fixed camera angle; the measured substance amount as information was sent to smart devices operating with Android Systems. The amount of information transmitted was shown in the user interface as the form of a percentile, thanks to an algorithm and the developed program. The algorithm in this software performs cropping and conversion to black and white format on the captured photo using image processing steps, and it calculates by scanning the black areas and proportionally these values to the area of the container, giving information about the level of the substance. It is possible to use the developed software as an alternative detection and evaluation system for object detection, image processing, and level control processes.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 3 (61), s. 46-57
Keywords: software; algorithm; data; image; objects; things; oprogramowanie; algorytm; dane; obraz; obiekty; rzeczy